Segni e simulacri : La lezione (giapponese) di Roland Barthes - Furlani, Simone (Scenari, 2021)
The first aim of this essay is to reconstruct the meanings of the concept of ‘simulacrum’ in Gilles Deleuze’s and Jacques Derrida’s philosophies, and to highlight its function in their critique of the tradition of thought which prioritizes “representation” and “presence”. In various ways their critique cannot avoid abstracting from the “becoming” of reality, even if both authors try to understand it in all its rich complexity. For this reason, the second aim of this essay is to give an account of a different and neglected perspective: that of Roland Barthes, which is focused on the concept of “empty sign”. Only by starting from this aporetic notion, both image and language can comprehend and express reality without binding themselves to logics and systems that are as much linear as external to reality itself.